2020
DOI: 10.1101/2020.11.04.364315
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 Infects Human Engineered Heart Tissues and Models COVID-19 Myocarditis

Abstract: Epidemiological studies of the COVID-19 pandemic have revealed evidence of cardiac involvement and documented that myocardial injury and myocarditis are predictors of poor outcomes. Nonetheless, little is understood regarding SARS-CoV-2 tropism within the heart and whether cardiac complications result directly from myocardial infection. Here, we develop a human engineered heart tissue model and demonstrate that SARS-CoV-2 selectively infects cardiomyocytes. Viral infection is dependent on expression of angiote… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 78 publications
0
37
0
Order By: Relevance
“…Despite reports of SARS-CoV-2 in some hearts with histologically proven myocarditis, 31 viral RNA has been undetectable in other COVID-19 myocarditis cases or did not correlate with sites of myocarditis. 102 , 105 , 112 , 113 Furthermore, acute myocarditis as defined by Dallas criteria has rarely been detected in COVID-19 nonsurvivors.…”
Section: Direct Myocardial Effectsmentioning
confidence: 70%
See 3 more Smart Citations
“…Despite reports of SARS-CoV-2 in some hearts with histologically proven myocarditis, 31 viral RNA has been undetectable in other COVID-19 myocarditis cases or did not correlate with sites of myocarditis. 102 , 105 , 112 , 113 Furthermore, acute myocarditis as defined by Dallas criteria has rarely been detected in COVID-19 nonsurvivors.…”
Section: Direct Myocardial Effectsmentioning
confidence: 70%
“…Cellular cathepsins can also process the S2’ position. In some cell types, such as human ventricular myocardium 30 and inducible pluripotent stem cell–derived cardiomyocytes, 31 , 32 where TMPRSS2 is expressed at very low levels, cathepsin inhibitors, rather than TMPRSS2 inhibitors, prevent SARS-CoV-2 cell entry. Thus, mechanisms involved in membrane fusion and cell entry may be cell-specific.…”
Section: Sars-cov-2 Viral Entry and Life Cyclementioning
confidence: 99%
See 2 more Smart Citations
“…A recent study has shown that the degree of both myocardial macrophage and lymphocyte infiltration correlates with the presence of SARS-CoV-2 infected cells in the interstitium and the duration of disease, but not with underlying medical conditions ( 22 ). Another study has found evidence of viral replication in cardiomyocytes in human engineered heart tissues ( 23 ). Further work is needed to resolve key issues relating to viral involvement of the myocardium, including the identification of the most commonly infected cell type ( 22 , 23 ).…”
mentioning
confidence: 99%